Programming with Quartz 2D and PDF graphics in Mac Os X - Gelphman, David; Laden, Bunny (Amsterdam ; Boston : Elsevier Morgan Kaufmann, 2006)
Written by members of the development team at Apple, Programming with Quartz is the first book to describe the sophisticated graphics system of Mac OS X. By using the methods described in this book, developers will be able to fully exploit the state-of-the-art graphics capabilities of Mac OS X in their applications, whether for Cocoa or Carbon development. This book also serves as an introduction to 2D graphics concepts, including how images are drawn and how color is rendered. It includes guidance for working with PDF documents, drawing bitmap graphics, using Quartz built-in color management, and drawing text. Programming with Quartz is a rich resource for new and experienced Mac OS X developers, Cocoa and Carbon programmers, UNIX developers who are migrating to Mac OS X, and anyone interested in powerful 2D graphics systems. * This is the definitive guide to the revolutionary graphics system of Mac OS X that uses the Portable Document Format (PDF) as the basis of its imaging model. * It contains the latest on programming with Quartz for Mac OS X version 10.4. * Carefully crafted and extensive code examples show how to accomplish most of the drawing tasks possible with Quartz.
Preface; 2. Introducing Quartz 2D; 3. Quartz 2D Drawing Basics; 4. Using Quartz 2D in Cocoa; 5. Using Quartz 2D in Carbon; 6. The Quartz Coordinate System and Coordinate Transforms; 7. Drawing with Paths; 8. Color, Alpha Transparency, and the Quartz Graphics State; 9. Data Providers and Data Consumers; 10. Drawing Images; 11. Image Masking; 12. Working with PDF Documents; 13. Quartz Memory Management Concepts; 14. Creating Bits; 15. Text; 16. Advanced Drawing Features; 17. Supporting PostScript Input Data; 18. Performance and Debugging; 19. Cocoa Application Topics and Tips; 20. Carbon Application Topics and Tips; 21. Python Drawing and Quartz 2D; 22. Using Quartz in Unix Tools; Appendices.
Includes bibliographical references and index.
Keywords: Computer graphics; Quartz (Electronic resource); Mac OS; Macintosh (Computer) -- Programming; Electronic books